1985
DOI: 10.1016/0014-5793(85)80004-1
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroaluminates activate transducin‐GDP by mimicking the γ‐phosphate of GTP in its binding site

Abstract: Fluoride activation of the cGMP cascade of vision requires the presence of aluminum, and is shown to be mediated by the binding of one AlF‐4 to the GDP/GTP‐binding subunit of transducin. The presence of GDP in the site is required: AlF4 − is ineffective when the site is empty or when GDPßS is substituted for GDP. This sensitivity to the sulfur of GDPßS suggests that AlF4 − is in contact with the GDP. Striking structural similarities between AlF4 − and PO4 −1 lead us to propose that AlF4 − mimics the role of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
192
0
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 417 publications
(205 citation statements)
references
References 17 publications
12
192
0
1
Order By: Relevance
“…First, we prepared cytoplasmic chaperonin in its ADP-bound form and showed that it was fully competent for binary complex formation. Second, we prepared cytoplasmic chaperonin in an ADP-P, form by using beryllium fluoride complexes as a structural analog of Pi (4,5); this form of chaperonin, which mimicks the transitional (ADP-Pi) state that is equivalent to the ATPbound form, completely failed to bind unfolded target protein (Fig. 7).…”
Section: Discussionmentioning
confidence: 99%
“…First, we prepared cytoplasmic chaperonin in its ADP-bound form and showed that it was fully competent for binary complex formation. Second, we prepared cytoplasmic chaperonin in an ADP-P, form by using beryllium fluoride complexes as a structural analog of Pi (4,5); this form of chaperonin, which mimicks the transitional (ADP-Pi) state that is equivalent to the ATPbound form, completely failed to bind unfolded target protein (Fig. 7).…”
Section: Discussionmentioning
confidence: 99%
“…Al/NaF is able to activate all G proteins by substituting for the terminal phosphate in the presence of GDP to mimic GTP (27). NCDC, an inhibitor of phospholipase C (15,24), was then administered to the media in a cumulative manner (from 10 to 200 M).…”
Section: Methodsmentioning
confidence: 99%
“…20,21 The increase in emission intensity which accompanies the activationdependent movement of the Switch II region into a hydrophobic pocket [1][2][3][4][5][6][7] provides a convenient and reliable method to assess the functional integrity of purified proteins. 22,23 Ga i contains two other Trp residues, W258 in the GTPase domain and W131 in the helical domain. Crystal structures show that the Trp in the helical domain of Ga i and Ga t proteins remains buried in both the inactive and active states, 3,4,6 and NMR studies have shown it to be refractory to activation.…”
mentioning
confidence: 99%